The effect of intensity of adsorption-desorption processes on the solutal convection near the surface of a drop in a horizontal channel - Birikh, Rudolf Voldemarovich; Rudakov, Rudolf Nikolaevich (Computational Continuum Mechanics, 2010)
Numerical experiment has been carried out to investigate the interaction between the Marangoni and gravitational convection in a horizontal rectangular channel filled with a fluid containing surface active substance and a drop of dissimilar fluid. The arising oscillatory mode of the solutal convection is analyzed for large values of the Schmidt number. The influence of the adsorption-desorption processes on the convective flow structure is determined in the framework of the surface-phase model. The stated two-dimensional initial boundary value problem is solved by the finite-difference method.
Keywords: solutal convection; surface phase; adsorption and desorption; oscillatory mode; finite-difference method